Konseling Individu Teknik Self Talk Untuk Mengatasi Perilaku Prokrastinasi Akademik Peserta Didik - Miftahul Jannah S. (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2025)
The purpose of this research is to determine the description of academic procrastination behavior in A at SMPN 33 Makassar, the causes of academic procrastination in A, and the handling of academic procrastination in A. This research uses a qualitative approach. Data collection was carried out through observation, interviews and documentation as well as using qualitative analysis from the Miles & Hubermen Model, namely data reduction, data presentation and drawing conclusions. The result is a description of A's academic procrastination behavior, namely often procrastinating in doing assignments, being lazy about doing and completing assignments, doing assignments when they are on deadline, being noisy in class, lacking focus when the teacher explains explanations and. The factors causing academic procrastination are low learning motivation, difficulty managing time, preferring to do more enjoyable activities, and from the experience gained, and to handle it, researchers apply self-talk techniques, namely students are able to find solutions to the problems they are experiencing, and students have the desire to change their behavior for the better to reduce the behavior of delaying assignments or academic procrastination.